The authority of the Queen of Aceh and the Sultan of Perak in tin trade negotiations with the Dutch 1640-1670 - Badri, Khairul Nizam Bin Zainal (Historia: Jurnal Pendidik dan Peneliti Sejarah, 2021)
Aceh reached its zenith, during the reign of Sultan Iskandar Muda Mahkota Alam. However he died at a young age, leaving an heir and legacy of enormous ruling power. Its main enemy, both in the military and in trade, is the European power in the Straits of Malacca. The Ruler of Aceh after his death had to deal with the Dutch colonialists who are interested in tin mining in the state of Perak in the Malay Peninsula. Perak at the time was under the auspices of Aceh. The main goal of this paper is to review the role and authority of the ruler of Aceh and Perak, when dealing with a Dutch ploy to monopolize the quarry. This study uses a qualitative method, with a fully literature approach. Based on the data analyzed, it was found that the Queen of Aceh and the Sultan of Perak managed to maintain the tin in Perak, from completely monopolized by the Dutch. The attitude of Queen of Aceh, and Sultan Perak's patience and diplomacy to treat the ills of the Dutch; finally resulted in the Dutch themselves have to bear the losses because of their greed by blockading the port of Aceh and Perak, who angered local merchants and foreigners.